Fate of patients with fixed subaortic stenosis after surgical removal. Issue 6 (June 1980) - Somerville, J; Stone, S; Ross, D
Abstract : Thirty-nine consecutive patients, aged 5 to 57 years, were followed for two to 15 years with serial haemodynamic studies after removal of fixed subaortic stenosis, which was never a "membrane". Two late deaths occurred, one sudden and one in congestive failure. Of 37 survivors, 25 were asymptomatic and could be classified as good or excellent if judged by well-being. Seven were symptomatic, two having had reoperation for fixed subaortic stenosis, and four needed long-term pacing. Evaluation, including the effect of isoprenaline, showed important dynamic obstruction in 17, five of whom redeveloped fixed obstruction. Seven had congestive features without outflow gradients, and 14 had neither congestion nor outflow obstruction. Complete assessment therefore confirmed that only 14 (36%) were haemodynamically satisfactory; two of them had permanent pacing, and four had had aortic valve surgery. Fixed subaortic stenosis should be removed early, when diagnosed, and completely before secondary myocardial changes occur. Patients however "well" need regular supervision and early haemodynamic assessment. The aortic valve, whether repaired, replaced, or untouched, remains a site for infective endocarditis for life. The fixed subaortic stenosis removed at operation may not be present in that form at birth, but acquired secondary to other congenital abnormalities which remain in the patient.